Comparative Study of the Diagnosis of Cutaneous Leishmaniasis by Slit Skin Smear and Skin Biopsy for Histopathology - Attiya Tareen , Syed Afaq , Anwar ul Haque (Journal of Rawalpindi Medical College, 2014)
Background: To compare slit skin smears for Leishmania tropica bodies on Romanowsky stains and skin biopsy for histopathology. Methods: In this comparative study Seventy six patients of cutaneous leishmaniasis (CL) were subjected to slit skin smears and skin biopsy and looked for LT bodies. These tests were than evaluated to see their efficacy in diagnosis of CL. The Z-test for proportion was used to check the percentage of diseased patients showing positive slit skin smear test and skin biopsy. Results: Favourable correlation between results of slit skin smear slides from the active edge of the lesion and histopathological examination of skin biopsy specimen was possible in fifty six patients. Skin biopsy was possible in fifty six patients and 3% were declared consistent with CL either on basis of presence of LT bodies or features suggestive of CL i.e plasma cell infiltrate and/or epitheliod cell granulomas with lymphocytes and giant cells. Slit skin smear was performed in 55 patients out of whom 76.03% showed presence of Leishmania tropica bodies on Giemsa’s staining. In 50.09% out of 55 patients both smear and skin biopsy was positive. In 18.02% patients, skin biopsy was positive but smear was negative. In none of the patients having negative biopsy, smear was positive. Positivity of slit skin smear test was 60% in sores of less than 04 months duration in contrast to 2.4% in lesions of greater than 8 months duration. Z= 2.648 shows that skin biopsy was more diagnostic for CL than slit skin smear. Conclusion: Skin Biopsy for histopathology showed 99% results. Since smear slides are easy to make, are cost effective and less time consuming, it should be preferably performed in lesions of less than 4 months duration.